Penerapan Network Development Life Cycle (NDLC) Dalam Pengembangan Jaringan Komputer Pada Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) Provinsi NTB - Rodianto Rodianto; Idham Idham; Yuliadi Yuliadi; Mohammad Taufan Asri Zaen; Wahyu Ramadhan (Fakultas Ilmu Komputer, 2022)
Information technology in recent years has become an absolute necessity, for all levels of society, especially the government, to support the exchange of information that is fast, easy, accountable, and has good service. BPKAD is one of the SKPDs in the NTB Province Government in charge of managing regional finances and assets that already have a computer network that mostly implements wireless-based applications, which are less than optimal for internet connections and information exchange so that they are not optimal in public services. Based on these problems, the researchers designed a computer network infrastructure that can be integrated between buildings at the BPKAD Office and other SKPD in the NTB province government. The design results presented can be used as considerations in order to support the development of e-government implementation. The network model used is the NDLC hierarchy and methodology. With a computer network, it can minimize connection constraints and be more optimal in bandwidth management, install filtering firewalls, limit users with negative content.Keyword: BPKAD; SKPD; E-Gorverment; NDLC; Bandwidth